Pharmacokinetic investigation of imatinib using accelerator mass spectrometry in patients with chronic myeloid leukemia - Boddy, Alan V; Sludden, Julieann; Griffin, Melanie J; Garner, Colin; Kendrick, John; Mistry, Pritesh; Dutreix, Catherine; Newell, David R; O'Brien, Stephen G (Clinical cancer research, 2007)
To investigate the potential use of accelerator mass spectrometry (AMS) in the study of the clinical pharmacology of imatinib. Six patients who were receiving imatinib (400 mg/d) as part of their ongoing treatment for chronic myeloid leukemia (CML) received a dose containing a trace quantity (13.6 kBq) of (14)C-imatinib. Blood samples were collected from patients before and at various times up to 72 h after administration of the test dose and were processed to provide samples of plasma and peripheral blood lymphocytes (PBL). Samples were analyzed by AMS, with chromatographic separation of parent compound from metabolites. In addition, plasma samples were analyzed by liquid chromatography/mass spectrometry (LCMS). Analysis of the AMS data indicated that imatinib was rapidly absorbed and could be detected in plasma up to 72 h after administration. Imatinib was also detectable in PBL at 24 h after administration of the (14)C-labeled dose. Comparison of plasma concentrations determined by AMS with those derived by LCMS analysis gave similar average estimates of area under plasma concentration time curve (26 +/- 3 versus 27 +/- 11 microg/mL.h), but with some variation within each individual. Using this technique, data were obtained in a small number of patients on the pharmacokinetics of a single dose of imatinib in the context of chronic dosing, which could shed light on possible pharmacologic causes of resistance to imatinib in CML.